Die vroeë kommunikasieontwikkeling van 'n groep babas met pediatriese MIV/VIGS in sorgsentrums - Isabel Bam; Alta Kritzinger; Brenda Louw (AOSIS, 2003)
The high prevalence and serious sequelae of the pediatric human immunodeficiency virus (HIV/AIDS) in South Africa pose great challenges for clinicians involved in early intervention to develop appropriate interdisciplinary programmes for primary prevention of transmission of the virus as well as secondary interventions directed at the early management of the unique combination of serious health problems, neuro-developmental needs and caregiving circumstances of the infants. Opsomming Die hoë prevalensie en ernstige gevolge van die pediatriese menslike immuniteitsgebrek-virus (MIV/VIGS) in Suid-Afrika stel groot uitdagings aan klinici betrokke by vroeë intervensie om toepaslike interdissiplinêre programme te ontwikkel vir primêre voorkoming van oordrag van die virus asook sekondêre intervensies gerig op die vroeë hantering van die babas se unieke kombinasie van ernstige Gesondheids-probleme, neuro-ontwikkelingsbehoeftes en versorgingsomstandighede. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.